Summary of Cows, missing milk markets and nutrition in rural Ethiopia - Hoddinott, John F.; Headey, Derek D.; Dereje, Mekdim (International Food Policy Research Institute, 2014)
In rural economies encumbered by significant market imperfections, farming decisions may partly be motivated by nutritional considerations, in addition to income and risk factors. These imperfections create the potential for farm assets to have direct dietary impacts on nutrition in addition to any indirect effects via income. We test this hypothesis for the dairy sector in rural Ethiopia, a context in which markets are very thin, own-consumption shares are very high, and milk is an important source of animal-based proteins and micronutrients for young children. We find that cow ownership raises children’s milk consumption, increases linear growth, and reduces stunting in children by seven to nine percentage points. However, we also find that the direct nutritional impacts of household cow ownership are less important where there is good access to local markets, suggesting that market development can substitute for household cow ownership.